Bioengineering a Future Free of Marine Plastic Waste - Sheth, Maya U.; Kwartler, Sarah K.; Schmaltz, Emma R.; Hoskinson, Sarah M.; Martz, E. J.; Dunphy-Daly, Meagan M.; Schultz, Thomas F.; Read, Andrew J.; Eward, William C.; Somarelli, Jason A. (Frontiers in Marine Science, 2019)
Plastic waste has reached epidemic proportions worldwide, and the production of plastic continues to rise steadily. Plastic represents a diverse array of commonly-used synthetic polymers that are extremely useful as durable, economically-beneficial alternatives to other materials; however, despite the wide-ranging utility of plastic, the increasing accumulation of plastic waste in the environment has had numerous detrimental impacts. In particular, plastic marine debris can transport invasive species, entangle marine organisms, and cause toxic chemical bioaccumulation in the marine food web. The negative impacts of plastic waste have motivated research on new ways to reduce and eliminate plastic. One unique approach to tackle the plastic waste problem is to turn to nature’s solutions for degrading polymers by leveraging the biology of naturally-occurring organisms to degrade plastic. Advances in metagenomics, next generation sequencing, and bioengineering have provided new insights and new opportunities to identify and optimize organisms for use in plastic bioremediation. In this review, we discuss the plastic waste problem and possible solutions, with a focus on potential mechanisms for plastic bioremediation. We pinpoint two key habitats to identify plastic-biodegrading organisms: 1) habitats with distinct enrichment of plastic waste, such as those near processing or disposal sites, and 2) habitats with naturally-occurring polymers, such as cutin, lignin, and wax. Finally, we identify directions of future research for the isolation and optimization of these methods for widespread bioremediation applications.